(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Emi l’okan (literally “it is my turn”) ideology, asserting power as an entitlement rather than democratic merit, conflicts with biblical teachings on leadership, justice, and morality. This study explores the ethical and theological dimensions of Emi l’okan, examining its impact on Nigeria’s political landscape. Through textual and qualitative analysis, it juxtaposes Emi l’okan principles with biblical precepts of humility, servant leadership, and ethical governance. The research offers insights for religious leaders, policymakers, and civil society to address entitlement-driven politics, promote ethical leadership, and foster democratic values, ultimately contributing to a more equitable political future for Nigeria.